Analisis Kepuasan Pasien Rawat Inap di Rumah Sakit Ibu dan Anak Kenari Graha Medika Bogor Jawa Barat - Prakasa, Sutan Bagas; Nurhakim, Bambang; Suhardi, Suhardi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
One of the health services that has a very important role in providing health services to the community is hospitals. The aim of this research is to find out the satisfaction of inpatients at the Graha Medika Kenari Bogor Mother and Child Hospital, which is a Type C Hospital. This research uses quantitative methods with a cross-sectional study approach (Cross Sectional Study). The population is all inpatients at Graha Medika Kenari Bogor Mother and Child Hospital. The sample was 250 people. The sampling procedure is to use accidental sampling technique. Data were analyzed using chi square analysis and logistic regression. The results show that responsiveness (p= 0.045), assurance (0.002), tangible (0.004), empathy (0.000), and reliability (0.011) have a relationship with inpatient satisfaction at the Graha Medika Kenari Bogor Mother and Child Hospital.